Speech by Brig. Gen. Dato' Prof. Dr. Kamarudin Hussin, UniMAP's Vice Chancellor during UniMAP-Industry Dinner (Zone II) - Kamarudin, Hussin, Brig. Gen. Dato' Prof. Dr. (Universiti Malaysia Perlis, 2010)
Event held at Dewan Perdana Felda, Kl.